ANALYSIS OF INTERNAL SERVICE QUALITY AND OUTPATIENT PATIENT SATISFACTION WITH A RATER APPROACH (RELIABILITY, ASURANCE, TANGIBLE, EMPATHY AND RESPONSIVNESS) IN INSTALLATIONS IN ISLAMIC HOSPITAL SURABAYA - Budhi Setianto; Akas Yekti Pulih Asih (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2021)
Patient satisfaction is a subjective value to the quality of services provided. Although subjective, there is still an objective basis, especially the patient's assessment which is based on past experience, education, psychological situation at that time, and the existing reality. The type and design of this research is a descriptive observational research that analyzes the patient's assessment of the service quality of the Outpatient Installation of the Islamic Hospital in Surabaya. Judging from the time of the study, this study included a cross sectional study. The population in this study were all patients at the Islamic Hospital Surabaya Outpatient Installation from an average of January, February and March 2020. The total population in this study was 14,000 patients based on the number of visits per month. during the first Quarter, starting from January to March 2020 with the slofin formula, 113 respondents were found. The five dimensions are: (1) Responsiveness, (2) Assurance, (3) Tangible, (4) Empathy and (5) Reliable is good and exceeds the standard than expected. The average satisfaction of all respondents is 8.56 / 85.6% this is close to the standard set by SPM customer satisfaction, which is 90%. Based on the demographics and characteristics of the following respondents, respondents who have satisfaction with service quality are as follows (1) Age 36-45 (2) Gender is Female (3) who has a residence distance of > 10 Km (4) with an insurance guarantor/ Institutions (5) with master's education served in the old building using the relationship test obtained sig < 0.005 so that it can be concluded that there is a relationship between perceived service quality and patient satisfaction, the higher the service quality felt by the patient, the higher the satisfaction felt by the patient.